Correction: Design and development of an irrigation monitoring and control system based on blynk internet of things and thingspeak. - Fahmy Rinanda Saputri; Ricardo Linelson; Muhammad Salehuddin; Danial Md Nor; Muhammad Imran Ahmad (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0321250.].